Development of a Model for Social Conflict Intentions in Urban Communities as Early Warning Systems - Suyono, Hadi; Lismawati, Lismawati (Universitas Ahmad Dahlan, 2024)
Social conflict in Indonesia is caused by stereotypes, social identity and prejudice. This issue prompts research aimed at developing a model for the intention of social conflict in urban communities with predictors of stereotypes, social identity, and prejudice as early warning systems. This research refers to both correlational and sequential models. The study subjects were high school students in Sebatik, Nunukan, North Kalimantan. The sampling technique employed was quota-cluster random sampling, resulting in the participation of 108 adolescents. Data collection utilized scales for stereotypes, social identity, prejudice, and social conflict intention. Data analysis was conducted using structural equation modeling, specifically confirmatory factor analysis. The results indicate that the model for the intention of social conflict in urban communities meets the criteria for goodness-of-fit statistics, as evidenced by the values of chi-square=44.1, df=59, P value=0.92543, and RMSEA=0.000. Based on the research findings, stereotypes and social identity shape prejudice, thereby reinforcing the intention of social conflict in urban communities.